Synthesis and crystal structures of Copper(II), Zinc(II), Lead(II) and Cadmium(II) Tetrazole-5-carboxylate complexes generated via in situ hydrolysis reaction - Kou, Jun-Feng; Su, M.; Zhang, Yu-Hong; Huang, Zhan-Dong; Ng, S.W.; Yang, G. (Verlag Z Naturforsch, 2010)
Four metal complexes, namely [Cu(2)(ttzCOO)(2)(H(2)O)(4)]center dot 4H(2)O (1), [Zn(2)(ttzCOO)(2)(H(2)O)6]center dot 2H(2)O (2), [Pb(ttzCOO)(H(2)O)(2)](n) (3), and {[Cd(ttzCOO)(H(2)O)]center dot 1/2H(2)O}(n) (4), where ttzCOO(2-) = tetrazole-5-carboxylate dianion, have been prepared by the reaction of the sodium salt of 1H-tetrazole-5-carboxylic acid ethyl ester in aqueous methanolic solution at room temperature with CuCl(2), Znl(2), Pb(NO(3))(2), or Cd(NO(3))(2), respectively. The compounds were characterized by elemental analysis, IR spectroscopy, TG-DSC analysis and single-crystal X-ray diffraction. While 1 and 2 are structurally similar dinuclear complexes, 3 and 4 exhibit a ID chain structure and a 3D polymeric framework, respectively.